Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.est.8b05245
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Imaging Reveals Holistic View of Soil Microenvironments

Abstract: The microenvironmental conditions in soil exert a major control on many ecosystem functions of soil. Their investigation in intact soil samples is impaired by methodological challenges in the joint investigation of structural heterogeneity that defines pathways for matter fluxes and biogeochemical heterogeneity that governs reaction patterns and microhabitats. Here we demonstrate how these challenges can be overcome with a novel protocol for correlative imaging based on image registration to combine three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 55 publications
(83 reference statements)
0
69
0
Order By: Relevance
“…Vidal et al (2018) have combined different spectroscopic and microscopic techniques to simultaneously gain information about the distribution of minerals and biomass in the vicinity of roots. More recently, Schlüter et al (2019), using a combination of X-ray µCT, fluorescence microscopy, scanning electron microscopy and nanoSIMS, were able to study the distribution of bacteria in a soil, and to show that they have a preference toward foraging near macropore surfaces and near fresh particulate organic matter. This pioneering interdisciplinary research opens the path toward the micro-and mesoscale analysis not just of the dynamics of soil organic matter, and related processes like priming or the storage and protection of carbon, which are eminently relevant in the context of global climate change, but also of other soil-borne processes of great practical importance, like the regulation of soil acidity and the binding of metals, about which various questions have remained unanswered, in spite of a sizeable research effort in the past (e.g., Tipping and Hurley, 1988;Tipping, 2002).…”
mentioning
confidence: 99%
“…Vidal et al (2018) have combined different spectroscopic and microscopic techniques to simultaneously gain information about the distribution of minerals and biomass in the vicinity of roots. More recently, Schlüter et al (2019), using a combination of X-ray µCT, fluorescence microscopy, scanning electron microscopy and nanoSIMS, were able to study the distribution of bacteria in a soil, and to show that they have a preference toward foraging near macropore surfaces and near fresh particulate organic matter. This pioneering interdisciplinary research opens the path toward the micro-and mesoscale analysis not just of the dynamics of soil organic matter, and related processes like priming or the storage and protection of carbon, which are eminently relevant in the context of global climate change, but also of other soil-borne processes of great practical importance, like the regulation of soil acidity and the binding of metals, about which various questions have remained unanswered, in spite of a sizeable research effort in the past (e.g., Tipping and Hurley, 1988;Tipping, 2002).…”
mentioning
confidence: 99%
“…A number of techniques have become available over the past few decades that allow detailed studies of the chemical interactions at the interface between microbial cells and their environment, including nanoscale secondary ion mass spectrometry, scanning transmission X-ray microscopy, neutron imaging, X-ray fluorescence spectroscopy, X-ray computed tomography, scanning electron microscopy coupled to energy-dispersive X-ray spectroscopy, IR and Raman spectroscopy and fluorescence spectroscopy [16][17][18][19][20][21][22]. Among these, IR spectroscopy is currently one of the most suitable tools to investigate the chemical interactions between microbial cells and their environments thanks to the detailed spectral information that can be obtained on organic compounds at a micrometer spatial resolution under ambient conditions [42].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for the slow progress in characterizing biogeochemical processes at the scale of microorganisms is the lack of appropriate methods. Current analytical techniques that allow microscopic imaging of chemical interactions between microbes and their environment require the sample compartment to be under vacuum and/or provide limited chemical information [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of different biogeochemical imaging methods, designated as correlative microscopy or correlative imaging, is increasingly used in life sciences (Caplan et al, 2011;Handschuh et al, 2013;Guyader et al, 2018). A few recent applications have demonstrated that there is a great potential for the application of correlative imaging in soil sciences (Hapca et al, 2011;Juyal et al, 2019;Kravchenko et al, 2019;Schlüter et al, 2019). Schlüter et al (2019) highlighted that a combination of different 2D techniques for chemical and microbial imaging, such as scanning electron microscopeenergy dispersive using X-ray (SEM-EDX) analysis and nanoscale secondary ion mass spectrometry (nanoSIMS) or fluorescence microscopy and X-ray µCT, can be used to reveal specific soil microenvironments and thus biogeochemical and physical processes in structured soil.…”
Section: Introductionmentioning
confidence: 99%